AUDIOVESTIBULAR SYSTEM, 5TH AND 7TH CRANIAL NERVE INVOLVEMENT IN LEPROSY - KOYUNCU, M; CELIK, O; OZTURK, OA; SAUNDERS, M (Multi-Science Publishing Co Ltd, 1993)
[Abstract Not Available]
XV World Congress of Otorhinolaryngology Head and Neck Surgery (ISTANBUL 93) -- JUN 20-25, 1993 -- ISTANBUL, TURKEY
Keywords: LEPROSY; AUDIOVESTIBULAR SYSTEM; TRIGEMINAL AND FACIAL NERVE